2015
DOI: 10.1063/1.4904420
|View full text |Cite
|
Sign up to set email alerts
|

High-energy-density electron jet generation from an opening gold cone filled with near-critical-density plasma

Abstract: By using two-dimensional particle-in-cell simulations, we propose a scheme for strong coupling of a petawatt laser with an opening gold cone filled with near-critical-density plasmas. When relevant parameters are properly chosen, most laser energy can be fully deposited inside the cone with only 10% leaving the tip opening. Due to the asymmetric ponderomotive acceleration by the strongly decayed laser pulse, high-energy-density electrons with net laser energy gain are accumulated inside the cone, which then st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It is shown that the laser intensity can be greatly boosted due to the coupling effect of nonlinear plasma effects and tightly focusing of the laser pulse in the cone424344. The strengthened laser ponderomotive force accelerates the electrons both radially and forward with considerable radiation emitted.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the laser intensity can be greatly boosted due to the coupling effect of nonlinear plasma effects and tightly focusing of the laser pulse in the cone424344. The strengthened laser ponderomotive force accelerates the electrons both radially and forward with considerable radiation emitted.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the NCD plasma is usually referred to as plasma with a density between n 0.1 c and n 10 . c In our scheme, NCD plasma is filled in the cone due to its efficient coupling with intense laser pulses [27]. In the following, we investigate the influences of the density of NCD plasma on the electron trapping and γ ray emission.…”
Section: The Density Of Ncd Plasmamentioning
confidence: 99%
“…Till now, lots of acceleration mechanisms have been proposed, such as the plasma wake field acceleration, 14 the target normal sheath acceleration (TNSA), [15][16][17][18] shock-wave acceleration at the front of the target, 19,20 and radiation pressure acceleration (RPA). 21,22 Although the maximum energy an ion can obtain from the laser pulse is proportional to the intensity of laser pulse and the cube root of acceleration time or distance theoretically, 23,24 yet the focused peak intensity of laser is always limited by the material breakdown threshold in practice, 25 and many other undesirable effects such as instabilities come to appear over long interaction time. 26 To date, a lot of improvements have been made by optimizing laser parameters, or designing new targets.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%